Military brownfields in the Czech Republic and the potential for their revitalisation, focused on their residential function - Hercik, Jan; Šimáček, Petr; Szczyrba, Zdeněk; Smolová, Irena (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2014)
One of the basic transformation processes of the period since 1989 has been that of demilitarisation. Among other things, one of its consequences is the emergence of abandoned military buildings and areas – so-called military brownfields. These kinds of brownfields have a large number of specific features to which their subsequent revitalisation must necessarily be adapted. Since a large number of these areas are situated within municipalities or are directly adjacent to them, it is essential for their revitalisation to be approached with great sensitivity. This contribution deals with chosen examples of Czech revitalised post-military areas with a special view to their residential function, which is presently their dominant functional use.
Keywords: military brownfield; revitalisation; residential function; Czech Republic